Who is Saving Whom? Equifinal Paths to a Meaningful Experience Design through Marine Watching Tours - Akhshik, Arash (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Marine protected areas are luring grounds for visitors who are willing to watch endangered species before they disappear forever. Hereafter, strategies to tackle the challenges of sustaining these fragile areas in one hand, and managing visitors in another are eminent. In this regard, visitor’s deportment that benefit self and visiting areas are notably well-researched. Yet, the conventional studies in the tourism-environmental domain often take a reductionist approach towards the complex issue of human behaviour that is criticized for its shortcomings. Therefore, to fill this gap, this dissertation develops and tests a theoretical model, drawing on the complexity theory and emerging concepts, i.e. dualistic-passion paradigm, and mindfulness notion, to predict the potential source of pro-environmental behaviour. The results indicate the complexity of the antecedents forming pro-environmental behaviour and the existence of contrarian cases that runs counter to the main effect in linear approaches. Therefore, following Fuzzy set Qualitative Comparative Analysis (fsQCA) of a sample from visitors to marine turtles in Cyprus, the study found seven unique causal recipes that lead to a high level of pro-environmental behaviour. Moreover, the study found 2 recipes that lead to low level of pro-environmental behaviour. Following predictive validity of the configural model, implications for theory and practice are presented. Further, guidelines for future research and limitations are discussed. Keywords: Pro-environmental Behaviour, Mindfulness, Passion, fsQCA, Marine Turtles, North Cyprus

ÖZ: Turizm-çevre ilişkisini inceleyen geleneksel çalışmalar, karmaşık insan davranışı sorununa genellikle indirgemeci bir yaklaşım benimsemesi dolayısı ile eleştirilmektedir. Bu nedenle, bu tez, çevre yanlısı davranışın potansiyel kaynağını tahmin etmek için karmaşıklık teorisi, dualistik tutku paradigması ve farkındalık gibi yeni kavramlardan yararlanarak teorik bir model geliştirmiş ve test etmiştir. Kıbrıs'ta deniz kaplumbağalarına gelen ziyaretçilerden oluşan bir örneklem ile Bulanık küme Nitel Karşılaştırmalı Analiz (fsQCA) yöntemi kullanılarak, yüksek düzeyde çevre yanlısı davranışlara yol açan yedi özgün nedensel tarif ortaya çıkarılmıştır. Tezin sonunda, uygulama için çıkarımlar ve daha fazla araştırma için öneriler verilmektedir. Anahtar Kelimeler: Çevre Yanlısı Davranış, Farkındalık, Tutku, fsQCA; Deniz Kaplumbağaları, Kuzey Kıbrıs
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2020. Supervisor: Prof. Dr. Ali Öztüren.
Keywords: Tourism; Tourism--Sustainable Tourism--Environmental Protection; Pro-environmental Behaviour; Mindfulness; Passion; fsQCA; Marine Turtles; North Cyprus